Studi Pengaruh Endorsement dan Advertising Campaign terhadap Brand Image Scarlett Whitening pada Instagram Bunga Cosmetics Kota Gorontalo - Zihan Putri Maharani Montu; Ramlan Amir Isa; Andi Juanna (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out how much influence Endorsements and Advertising Campaigns have on Scarlett Whitening's Brand Image on Instagram Social Media (Study on Scarlett Whitening Bunga Cosmetics Agent, Gorontalo City)." The sampling technique in this research uses non-probability sampling techniques. The data collection technique in this research used a questionnaire with a population of Scarlett Whitening Gorontalo Instagram followers, namely 6,525 people. The sample in this research was 98 respondents. The analytical test tool used in testing this research is multiple linear regression. The data analysis method uses the SPSS 22 application. Based on research, the results of multiple regression analysis show that the simultaneous test results of the Endorsement and Advertising Campaign variables have a significant effect on Brand Image. Based on the partial test results, the Endorsement variable does not have a significant effect on Brand Image while the Advertising Campaign variable has a significant effect on Brand Image. The independent variables, namely Endorsement and Advertising Campaign, are able to explain or influence the dependent variable, namely Brand Image, by 69.1%. Meanwhile, the remaining 30.9% is explained by other factors or variables that were not involved in this research.